(untitled) (Journal of actual problems of jurisprudence, 2018)
The article analyzes the role of civil society in the formation of anti-corruption culture and anti-corruption consciousness in the Republic of Kazakhstan. Civil society as the highest form of self-organization of individuals can provide a person all the conditions for the development of a high level of legal awareness, which, simultaneously, is an indispensable factor in the functioning of such a society. We believe that public activity and personal initiative are important circumstances in the creation of a civil society and a rule of law state based on the legal consciousness of the individual. It is they who give the main impetus to democratic reforms in the country and in society. The desire to work in a certain direction and, in the end, the very work itself depends on the processes taking place in the individual consciousness. Therefore, we must pay attention to the fact that all individual actions necessary for the development of civil society are revealed in legal ideology and psychology. That is why civilian legal consciousness, as the main driving force of social transformations, is of paramount importance for the formation of civil society along with general democratic, economic and political reforms. Key words: civil society, civil society institutions, legal education, legal culture, legal awareness, corruption, fighting corruption, measures to prevent corruption, causes of corruption.